Is One Watchdog Better Than Three? International Experience with Integrated Financial Sector Supervision. (IMF working paper, 2006)
Over the past two decades, there has been a clear trend toward integrating the regulation and supervision of banks, nonbank financial institutions, and securities markets. This paper reviews the international experience with integrated supervision. We survey the theoretical arguments for and against the integrated supervisory model, and use data on compliance with international standards to assess the validity of some of these arguments. We find that (i) full integration is associated with higher quality of supervision in insurance and securities and greater consistency of supervision across sectors, after controlling for the level of development; and (ii) fully integrated supervision is not associated with a significant reduction in supervisory staff.